Principles of macroconomics - Arnold, Roger A. (Mason, OH : South-Western/Cengage Learning, 2011)
The book deals on general aspects of macroeconomics but this edition is revised to include comprehensive coverage of the financial and economic crisis available, with self-help materials.
Includes bibliographical references and index.
nif 26/04/13
Loans
Keywords: Macroeconomics; Macroeconomics - principles